University professional training tourism in La Libertad region - Peru and its relationship to the training needs of the sector tourism - Iberico Díaz, Marcia Adriana (2017)
The knowledge and expertise contribute to the development of society. Tourism provides new insights for theadvancement of the world, but for the adequate development and achievement of this activity it is necessary anintegral, holistic and systematic view. Therefore, it is necessary to have a qualified human capital especially inmanagement. The aim of this paper is to determine the relationship between vocational training provided byuniversities of tourism in La Libertad Region and the training needs of the sector. The methods used areethnographic and analytic-synthetic, using interviews and surveys at the responsible sector. The resultsdemonstrate that the universities in the region are focused on technical training-operational and that the sector hasa limited view of their real needs regarding the capabilities and skills with which workers must have